2017
DOI: 10.15578/squalen.v12i3.290
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aflatoxin B1 in Commercial Dried Fish from Some Regions of Java

Abstract: The purpose of this study is to study the prevalence of aflatoxin B1 in commercial dried salted fish and other related information. A total of 150 samples were classified into 3 groups, based on the salt content. Low salt content (0-5%) were dried anchovies (Stolephorus sp.) and commerson's anchovy (Stolephorus commersonii); moderate salt content (6-10%) were medan anchovy (Stolephorus bataviensis) and whipfin silverbiddy (Gerres filamentosus) while high salt content (>10%) were moonlight gouramy (Trichogaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…juga didapati mengkontaminasi ikan asap selama penyimpanan suhu ruang (Ayeloja et al, 2018). Indriati et al (2017) mendapati total 1,00-1,70 log CFU/g Aspergillus flavus pada sampel ikan teri asin dengan rentang kadar air 11,59-44,72% selama penyimpanan suhu ruang. Penanganan yang dapat dilakukan untuk mencegah tumbuhnya kapang patogen pada produk ikan kering seperti katsuobushi dapat dilakukan dengan pemberian edible coating.…”
Section: Katsuobushiunclassified
“…juga didapati mengkontaminasi ikan asap selama penyimpanan suhu ruang (Ayeloja et al, 2018). Indriati et al (2017) mendapati total 1,00-1,70 log CFU/g Aspergillus flavus pada sampel ikan teri asin dengan rentang kadar air 11,59-44,72% selama penyimpanan suhu ruang. Penanganan yang dapat dilakukan untuk mencegah tumbuhnya kapang patogen pada produk ikan kering seperti katsuobushi dapat dilakukan dengan pemberian edible coating.…”
Section: Katsuobushiunclassified
“…This semiquantitative analysis defined the risk of consumers that consumes 1 g salted fish contaminated with A. flavus and aflatoxin B1. Indriati et al (2017) found that 11 of 77 salted fish samples were contaminated with A. flavus (Figure 1). Dominant contamination was found from samples taken from West Java (6 samples).…”
Section: Exposure Assessment and Risk Characterization;mentioning
confidence: 99%
“…Other important contributing factors in the development of HCC, in addition to HBV or HCV Moonlight gouramy (Channa striata ) 1.0-1.60 24.60 -27.0 Table 2. Concentration of A. flavus in dried salted fish samples (Indriati et al 2017) infection and aflatoxin exposure, are genetic characteristics of the virus, consumption…”
Section: Hazard Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A. flavus has been known as aflatoxin producer, a toxin that can affect the mechanism of the liver in humans, mammals, and poultry, thus becoming a factor causing liver cancer [ 11 , 12 ]. A. flavus that has been reported is also found in the preserved fishery products, such as semidried and salted fish products [ 13 , 14 ]. Hence, this research is aimed at determining the antifungal activity of water extract of old and fermented seed of P. edule against toxigenic A. flavus .…”
Section: Introductionmentioning
confidence: 99%